PENGELOLAAN PENDIDIKAN DAN PEMBELAJARAN BERBASIS POTENSI LOKAL - Husnul Bahri (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
Management education and learning have a strategic role in improving human resources as mandated by the ideal of the nation  is “the nation”,  which  was followed  by the function  of education is to equip  humans to be  intelligent,  skilled,  and  responsible. A thought  that  management education study  program organized excavated from the needs of the people associated with the local potential that existing resources, evolved from the tradition  of local knowledge sector  in a particular region. The impact  is the effectiveness of education and learning management model  based on local potentials can be effectively implemented and effective. To see it is based on a positive response from all parties involved in the activities, and the reaction of the learning outcomes regarding cognitive, affective, and psychomotor